Strategic aspects of management of gas industry in the system of regional development - Писар, Н. Б. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Theoretical, methodological and practical aspects of strategic management, monitored topical issues of the gas sector of Ukraine suggested the strategic direction of the gas sector of Ukraine, the necessity of developing a strategy of competitive performance level of priority sectors to ensure decent position of the national economy in the international division of labor.